"LINGUO-DIDACTIC FEATURES OF PHRASEOLOGICAL UNITS IN ENGLISH AND UZBEK" - Рахматова Зулхумор Мамитхоновна (Journals Park Publishing, 2023)
In this article, the interdependence and difference of Uzbek and English phraseological units, their translation forms are studied comparatively.
Keywords: phraseology, synonymy, antonymy of phraseological units, idiom, proverb.